Malthus v. Bailey on the measure of value: a lesson in methodological humility - Glenn Hueckel (Claremont McKenna College, Department of Economics, 2002)
That Malthus was guilty of egregious error in his claim to have established the labor-commanded magnitude as an invariable unit of value is well-known. Even his modern biographer could appeal only to a kink or a crotchet, some kind of cerebral block to excuse Malthus's persistent failure to recognize the manifestly tautological character of his position. Yet the familiar form of Malthus's argument, as it appeared in his later work, differed in several respects from its earliest statement in the first edition of his Principles. In this essay we trace out the several changes made to Malthus's argument, often in response to his many critics; and we find in the midst of those alterations a common characteristic that serves to reveal the character of that kink or crotchet: an obsession with mathematical operations producing a unit outcome. We draw two lessons from this sorry episode in our history. First, the sterility of the debate between Malthus and his critics serves to highlight the central importance of a precise and commonly understood vocabulary of scientific expression. This was, it is true, no more than a dispute over words; but as they are the vessels of our thoughts, words-of precise and commonly understood meaning-are critical to the progress of a science. Second, the heat of that debate highlights the insidious capacity of practitioners to mistake for scientific principles what are no more than intricate series of definitions, a lesson which, when taken seriously, cannot fail but to impart a salutary methodological humility.
Keywords: 330; Werttheorie; Dogmengeschichte